Lithuanian bibliophiles in the XVIII century - Vladimirovas, Levas (Knygotyra, 2024)
The level of culture, education, publishing, and book dissemination influences the number of bibliophiles in society. During the Age of Enlightenment, better conditions for the collection of books were created in Lithuania. However, the bibliophiles in Lithuania were mostly aristocrats. They created wonderful collections in their palaces. Later, most of those books enriched various state and research libraries. The article deals with the bibliophiles who lived in the territory of the Grand Duchy of Lithuania in the 18th century. The Lithuanian nobility living outside Lithuania is not discussed in the article. Data about the Lithuanian bibliophiles were found in published and unpublished materials from Polish, Russian, and Lithuanian archives, as well as in different historical works, reference books, and bibliographies. The article characterizes the greatest and lesser book collections that belonged to the members of the Radvilas, Sapiehas, Chreptowiczs, Oginskis, Pacs, Bżostowskis, Kosakovskis, Łopacińskis, Plateris, and other families. The author presents short biographical data about the bibliophiles, reveals the origin of their collections, their size, contents, value, management peculiarities, features of the bookplates and book signs, and traces the later fate of the collections when possible. Besides the collections of the Lithuanian nobility, the author analyzes the book collections of Vilnius University professors (T. Zebrauskas, D. Pilchovskis, S. Bisius, J. E. Giliert, G. Forster, J. Sartorius), monks and priests, as well as the rare cases of book collections owned by city-dwellers. Among the greatest bibliophiles, one can find not only men but women as well. Some of them, like Uršulė Višnioveckaitė-Radvilienė, Elena Radvilienė, Žozefina Radvilienė-Masalskienė, Konstancija Radvilaitė-Sapiegienė, Ona Sapiegaitė-Jablonovskienė, Teofilė Jablonovskytė-Sapiegienė, Aleksandra Czartoryska-Ogińska, Ona Platerytė, and Judita Jelenskytė-Raes, built valuable collections according to their interests or maintained and developed inherited collections. It is evident that during the 18th century, book collection and maintaining libraries was a matter of fashion among the noble families in Lithuania. Some of the bibliophiles were educated in the best European universities and took a genuine interest in cultural activities as well as books. Others just followed a fashionable trend.